2020
DOI: 10.1186/s12909-020-02091-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy students’ perspectives on the initial implementation of a teaching electronic medical record: results from a mixed-methods assessment

Abstract: Background: Electronic medical records (EMRs) have been used for nearly three decades. Pharmacists use EMRs on a daily basis, but EMRs have only recently been incorporated into pharmacy education. Some pharmacy programs have implemented teaching electronic medical records (tEMRs), but best practices for incorporating tEMRs into pharmacy education remain unknown. The objectives of this study were to 1) assess pharmacy students' views and experiences with a tEMR; and 2) identify current learning activities and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…One mixed-method study comprised of focus groups and surveys reported that overall, virtual EMR trainings were favorable with half of participants agreeing that teaching sessions on the EMR enhanced learning. 18 A simulation EMR training course on a platform identical to the EMR system used at the facility was modestly beneficial in helping students use the EMR; however, the course was time intensive and took place over many weeks and thus required significant resources. 19 Another training program used a case study on severe sepsis as a method of teaching the EMR, which was well received by the students and was mostly limited by the in-person format.…”
Section: Resultsmentioning
confidence: 99%
“…One mixed-method study comprised of focus groups and surveys reported that overall, virtual EMR trainings were favorable with half of participants agreeing that teaching sessions on the EMR enhanced learning. 18 A simulation EMR training course on a platform identical to the EMR system used at the facility was modestly beneficial in helping students use the EMR; however, the course was time intensive and took place over many weeks and thus required significant resources. 19 Another training program used a case study on severe sepsis as a method of teaching the EMR, which was well received by the students and was mostly limited by the in-person format.…”
Section: Resultsmentioning
confidence: 99%
“…However, the question remains whether customized educational training programs for EMR improvement would contribute to clinical documentation, medical education, and patient safety. Literature about EMR training discusses its application for medical students or for clinicians in a single department [6,17,18,19]. Few studies investigated the differences in EMR quality between residents from different departments.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the pedagogical approaches being used to integrate EHRs into curricula and their outcomes shows that teaching alongside EHRs positively impacts student confidence, preparedness for clinical practice and improved communications skills. 10 We believe that such work will not only equip students and clinicians to put data in the record to better use and write entries benefiting their colleagues and patients, but also inspire them to consider how electronic medical records and systems could evolve in the future beyond their current functions to become a collaborative tool to enhance and encourage better patient-centred care.…”
mentioning
confidence: 99%
“…We recognise the importance of developing such skills regardless of professional identity, and that using digital technologies requires multidisciplinary working to bring about effective digital collaboration and communication. Investigating the pedagogical approaches being used to integrate EHRs into curricula and their outcomes shows that teaching alongside EHRs positively impacts student confidence, preparedness for clinical practice and improved communications skills 10…”
mentioning
confidence: 99%